Analysis of Mobile-Based Geometry Learning Media Design for Middle School Students - Gini Permatasari, Ambar; ., Nurjanah; Andrian, Rian (KnE Social Sciences, 2024)
Nowadays, a lot of students find mathematics a boring and difficult subject to follow. Geometry is one of the fields of study in middle school mathematics which gets a larger portion to be studied by students at school compared to other materials such as algebra, numbers, statistics, and probability. This is due to many concepts contained in geometry and its abstract nature, so in teaching geometry, the teacher needs to plan it well so that it can be understood by students. However, geometry is still considered one of the most difficult materials for students to understand. The use of mobile-based learning media can be an alternative as a solution to make students more active in the learning process. Based on the above background, this research will analyze and design mobile-based geometry learning media for middle school students. The research will be carried out using the design thinking method to get the needs of the target user. Design thinking is a non-linear, iterative process that teams use to understand users, challenge assumptions, redefine problems, and create innovative solutions to prototype and test. Keywords: mobile-based learning, geometry, media design, middle school st